Livestock Greenhouse Gas Emissions in Ethiopia by region: a graphic summary - Bateki, Christian A; Wilkes, Andreas; Wassie, Shimels Eshete (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This report is based on the Inventory of GHG emissions from cattle, sheep, and goats in Ethiopia (1994-2018) calculated using the IPCC Tier 2 approach approved by the Ministry of Agriculture (Wilkes et al., 2020). That national inventory report presented in detail the data sources, methods and results for GHG emissions from cattle, sheep and goats at the national level. This report summarizes the main results for each region in Ethiopia.